Answer:
-12x + 24
Step-by-step explanation:
Using multiplication signal rules, it is found that:
A: Emma's statement is always false.
B: The result is always negative.
C: Emma's statement is always true.
The rule used for this exercise is as follows:
- When two numbers of different signals are multiplied, the result is negative.
- When two numbers have the same signal, the result is positive.
Part A:
- Three numbers are multiplied, all negative.
- The multiplication of the first two result in a positive number.
- Then, this positive number is multiplied by a negative number, and the result will be negative, which mean that Emma's statement is always false.
Two examples are:
![-2.5(-3.8)(-2) = 9.5(-2) = -19](https://tex.z-dn.net/?f=-2.5%28-3.8%29%28-2%29%20%3D%209.5%28-2%29%20%3D%20-19)
![-2.5(-2)(-0.7) = 5(-0.7) = -3.5](https://tex.z-dn.net/?f=-2.5%28-2%29%28-0.7%29%20%3D%205%28-0.7%29%20%3D%20-3.5)
Part B:
The rule is that the result is always negative.
Part C:
- The multiplication of the first two negative numbers result in a positive number.
- Then, this positive number is multiplied by another positive number, and the result will be positive, which mean that Emma's statement is always true.
Two examples are:
![-2.5(-3.8)(2) = 9.5(2) = 19](https://tex.z-dn.net/?f=-2.5%28-3.8%29%282%29%20%3D%209.5%282%29%20%3D%2019)
![-2.5(-2)(0.7) = 5(0.7) = 3.5](https://tex.z-dn.net/?f=-2.5%28-2%29%280.7%29%20%3D%205%280.7%29%20%3D%203.5)
A similar problem is given at brainly.com/question/24764960
The answer is A because when you plug in the points into the distance formula, you will get square root of 17 squared plus 17 squared. Hope this helps!
<h2>
Steps:</h2>
Here are the steps to convert an equation to its inverse:
- Change f(x) to y
- Switch the positions of x and y
- Solve for y
- Change y to f^-1(x)
Firstly, do the first two steps:
![x=4y+3](https://tex.z-dn.net/?f=x%3D4y%2B3)
Next, let's solve for y. Subtract 3 on both sides:
![x-3=4y](https://tex.z-dn.net/?f=x-3%3D4y)
Next, divide both sides by 4:
![\frac{1}{4}x-\frac{3}{4}=y](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7Dx-%5Cfrac%7B3%7D%7B4%7D%3Dy)
<h2>Answer:</h2>
Finally, change y to f^-1(x) and your final answer will be:
, or <u>the second option.</u>
Ok what is the rest of the question